Multiple recurring gastric erosions/aphthous ulcers). Issue 8 (August 1976) - Morgan, A G; McAdam, W A; Pyrah, R D; Tinsley, E G
Abstract : Five patients are described who had repeated endoscopy because of continuing dyspeptic symptoms associated with a negative barium meal. They were found to have multiple recurring gastric erosions (aphthous ulcers). No common aetiological factor could be found, although four of these patients did have a mild or moderatley active superficial chronic gastritis. Conventional peptic ulcer therapy failed to control either symptoms or ulceration. Two patients finally came to gastric surgery (highly selective vagotomy), which resulted in the relief of symptoms and healing of the gastric aphthous ulceration.